Higher education service learning with First Peoples of Australia - Bennett, Dawn; Sunderland, N.; Power, A.; Bartleet, B. (Higher Education Research and Development Society of Australasia, Inc, 2015)
Australian higher education institutions face increasing pressure to institute Aboriginal and Torres Strait Islander culture at every level of activity. In this paper, which takes as its context a three-university service-learning initiative with First Peoples of Australia, we argue that service-learning opportunities develop students who are more culturally responsive, adaptable and aware. In this instance we position service learning as a strategy through which Australian universities and colleges might promote Indigenous cultural content for students, faculty and the broader community. We report the experiences of a funded, arts-based service learning initiative in which creative arts students (n=70) and pre-service teachers (n=37) worked with over 290 Aboriginal community members in urban, rural and remote areas of Australia. The study adopted an action research approach and we combined a range of conceptual-theoretical resources with the voices and experiences of the students, academic researchers and community members. Our study data confirmed the potential for service learning to build valuable intercultural competencies amongst higher education students, fostering critical engagement with racial politics and a shift in extant views of cultural diversity. Participating students developed a deeper awareness of their past experiences and a greater sensitivity towards forms of social and cultural oppression. Deeper critical engagement with the issues faced by Aboriginal and Torres Strait Islander communities prompted students to be more responsive in their critiques of the cultural politics of their own educational experiences. As they gained confidence and self-assuredness, students learned to draw